The Family Welfare Programs (Tim Penggerak Pemberdayaan Kesejahteraan Keluarga) Strategy For Enhancing Womens Empowerment in The Jatigono Village - Chilmy, Nur Wahdatul; Khotimah*, Khusnul; Rinawati, Evi (Universitas Syiah Kuala, 2024)
The condition of women in Jatigono Village is that there are still many who have low education, do not have jobs, have low economic status, lack knowledge about clean and healthy living behavior, and have families that are not harmonious or not yet prosperous. The Family Empowerment and Welfare Mobilization Team has an important role in empowering women, through 10 main programs. The aim of this research is to observe and analyze the Strategy of the Empowerment and Family Welfare Team in Increasing Women's Empowerment in Jatigono Village, Kunir District, Lumajang Regency. This research uses descriptive qualitative. Data collection techniques start from observation, interviews and documentation. The data analysis technique uses the Interactive Analysis Model from Miles and Huberman, namely data reduction, data display and Conclusing Drawing. The research results show that the Implementation Strategy of the Family Empowerment and Welfare Mobilization Team in Increasing Women's Empowerment in Jatigono Village has been running and has been successful, but there are still several factors that are not appropriate in its implementation, namely the lack of awareness of women to take part in programs held by TP PKK. The efforts made by the Jatigono Village TP PKK are to provide education and training to improve the quality of women's knowledge, insight, science and experience and the Jatigono Village government allocates resources in the form of funds and facilities to support TP PKK activities